Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To get rid of [tex] x^{3} [/tex], you have to take the third root of both sides:
[tex] \sqrt[3]{x^{3}} = \sqrt[3]{1} [/tex]
But that won't help you with understanding the problem. It is better to write [tex] x^{3}-1 [/tex] as a product of 2 polynomials:
[tex] x^{3}-1 = (x-1)\cdot (x^{2} +x +1) [/tex]
From this we know, that [tex] x-1 = 0 => x = 1 [/tex] is the solution. Another solutions (complex roots) are the roots of quadratic equation.
[tex] \sqrt[3]{x^{3}} = \sqrt[3]{1} [/tex]
But that won't help you with understanding the problem. It is better to write [tex] x^{3}-1 [/tex] as a product of 2 polynomials:
[tex] x^{3}-1 = (x-1)\cdot (x^{2} +x +1) [/tex]
From this we know, that [tex] x-1 = 0 => x = 1 [/tex] is the solution. Another solutions (complex roots) are the roots of quadratic equation.
[tex]x^3-1=0\\
(x-1)(x^2+x+1)=0\\
x-1=0\\
x=1\\
x^2+x+1=0\\
x^2+x+\frac{1}{4}+\frac{3}{4}=0\\
(x+\frac{1}{2})^2=-\frac{3}{4}\\
x+\frac{1}{2}=\sqrt{-\frac{3}{4}} \vee x+\frac{1}{2}=-\sqrt{-\frac{3}{4}}\\
x=-\frac{1}{2}+i\frac{\sqrt3}{2} \vee x=-\frac{1}{2}-i\frac{\sqrt3}{2}\\
x=-\frac{1-i\sqrt3}{2} \vee x=-\frac{1+i\sqrt3}{2}\\\\
x=\{1,-\frac{1-i\sqrt3}{2},-\frac{1+i\sqrt3}{2} \}[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.